Wrong place, wrong time: climate change-induced range shift across fragmented habitat causes maladaptation and declined population size in a modelled bird species - Cobben, Marleen M. P.; Verboom, Jana; Opdam, Paul F. M.; Hoekstra, Rolf F.; Jochem, René; Smulders, Marinus J. M. (Global change biology, 2012)
Many species are locally adapted to decreased habitat quality at their range margins, and therefore show genetic differences throughout their ranges. Under contemporary climate change, range shifts may affect evolutionary processes at the expanding range margin due to founder events. In addition, populations that are affected by such founder events will, in the course of time, become located in the range centre. Recent studies investigated evolutionary changes at the expanding range margin, but have not assessed eventual effects across the species' range. We explored the possible influence of range shift on the level of adaptation throughout the species' total range. For this we used a spatially explicit, individual‐based simulation model of a woodland bird, parameterized after the middle spotted woodpecker ( Dendrocopos medius) in fragmented habitat. We simulated its range under climate change, and incorporated genetic differences at a single locus that determined the individual's degree of adaptation to optimal temperature conditions. Generalist individuals had a large thermal tolerance, but relatively low overall fitness, whereas climate specialists had high fitness combined with a small thermal tolerance. In equilibrium, the populations in the range centre were comprised of the specialists, whereas the generalists dominated the margins. In contrast, under temperature increase, the generalist numbers increased at the expanding margin and eventually also occupied the centre of the shifting range, whereas the specialists were located in the retracting margins. This was caused by founder events and led to overall maladaptation of the species, which resulted in a reduced metapopulation size and thus impeded the species' persistence. We therefore found no evidence for a complementary effect of local adaptation and range shifts on species' survival. Instead, we showed that founder events can cause local maladaptation which can amplify throughout the species' range, and, as such, hamper the species' persistence under climate change.